A case of schizophrenia with congenital color vision deficiency: From the perspective of color universal design to promote medication adherence - Kensuke Miyazaki; Michiko Uchiyama; Chieko Tsushima; Kentarou Fujimoto (Wiley, 2022)
Abstract Color‐blindness, or more accurately, color vision deficiency (CVD), which is the inability or decreased ability to distinguish different colors, is one of the commonest visual disorders. Patients with schizophrenia usually have multiple types of visual processing impairments, including color vision impairments. Here, we present a case of schizophrenia with congenital CVD. The patient was aware of his color deficiency since elementary school. We assessed his ability to distinguish medicines based on their color, including those that he had been previously prescribed. Although he could distinguish all of the tablets, he could not distinguish the color of the blister packs, specifically that of the bromazepam 2 mg pack (green) from the 1 mg pack (red). This case suggests that CVD patients might misunderstand the color of medications, which might lead to medication errors, or poor drug adherence. The color universal design principle should be considered when designing tablets and their blister packs, in order to improve medication adherence.